Synthesis and characterization of PVA-Graphene-Ag nanocomposite by using laser ablation technique. (July 2020) - Mohammed, Musaab Khudhur; Al-Dahash, Ghaleb; Al-Nafiey, Amer
Abstract: The PVA-G-Ag nanocomposite have been synthesized effectively by pulsed laser ablation liquid (PLAL) as a considered to be environmentally friendly and free of residues from chemical reactions. The high excellence silver plate (99.99%) and graphite plate (99.99%) was immersed in the polyvinyl alcohol (PVA) solution and irradiated with the Nd-YAG laser at wavelength 1064 nm, power 160 mJ for the silver plate and 80mJ for graphite plate, reiteration rate 6 Hz, 10 ns pulse width and 300 pules for graphite plate and 700 pulse for silver plate. The pure of PVA, PVA-Graphene and PVA-Graphene-Ag nanocomposite were investigated using UV-VIS spectroscopy, FTIR and SEM. The absorption spectra of PVA-Graphene-Ag nanocomposite show the presence of two peaks one 0.4 at 272 and second 0.47 at 403 nm. The optical energy gap (Eg) decreased from 5eV of a pure PVA to 4.6eV of a PVA-G-Ag for indirect allowed transition and therefore, decreased from 4.4eV of a pure PVA to 4.1eV of a PVA-G-Ag for indirect forbidden transition. The transmittance and absorption coefficient have been determined. The SEM images confirmed that homogenous composite without aggregation of the components. The average size of nanoparticles of GNPs and AgNPs for PVA-G and PVA-G-Ag nanocomposite was 130 and 115 nm respectively. The FTIR has demonstrated that the connection between the graphene, silver and polymer network was enough to have stable nanocomposite. This investigation demonstrates that the pulse laser ablation decent instrument to decorated metals on the graphene with the presence of the polymer.